1993
DOI: 10.1159/000133515
|View full text |Cite
|
Sign up to set email alerts
|

Rapid immunophenotypic characterization of chromosomally aberrant cells by the new FICTION method

Abstract: Recently, we have presented a new technique for immunophenotyping cells that have numerical chromosome aberrations. We referred to this method as “Fluorescence-Immunophenotyping and Interphase Cytogenetics as a Tool for Investigation of Neoplasms” (FICTION). We present here an advanced FICTION method with three-color staining and improved sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…7b,d,f). By combining immunofluorescent staining for cyclin B1 with FISH for t(11;14) (FICTION methodology) 17 it was found that many of the cyclin B1 positive cells contained the fusion signal and thus belonged to the tumor cell population (data not shown).…”
Section: Validation Of the Differential Gene Expression In Another Sementioning
confidence: 99%
“…7b,d,f). By combining immunofluorescent staining for cyclin B1 with FISH for t(11;14) (FICTION methodology) 17 it was found that many of the cyclin B1 positive cells contained the fusion signal and thus belonged to the tumor cell population (data not shown).…”
Section: Validation Of the Differential Gene Expression In Another Sementioning
confidence: 99%
“…The MAC method was based on the techniques of Stenman et al (1975), who used immunostaining on cytospin preparations. Several MAC modifications and related techniques have emerged since 1984 (Anastasi et al, 1991;Haas et al, 1987;Henn et al, 1990;Kibbelaar et al, 1992;Köller et al, 1986Köller et al, , 1989Mullink et al, 1989;Perry & Thomson, 1986;Price et al, 1992;Schlegelberger et al, 1992;van den Berg et al, 1991;Weber-Matthiesen et al, 1993a. For phenotypic analysis some of these employ only cytochemical techniques (Anastasi et al, 1991) and others use only immunocytochemical techniques .…”
Section: Hodgkin's Lymphoma (Hl)mentioning
confidence: 99%
“…In 1992, Weber-Matthiesen et al (7,8) developed a method called Fluorescence Immuno-phenotyping and Interphase Cytogenetics as a Tool of the Investigation of Neoplasm. However, based on images presented in those reports, it was considered that improvements in the technique used for detection were required and it has yet to become a universal method.…”
Section: Double-detection -------------------------------------------mentioning
confidence: 99%